Implementing Caliphate Values in the Qur’an through Zero Waste in an Ecological Tafsir Study - Bimawan, Henri; Muhammad, Bill Zam zam Multazam (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
Environmental degradation and waste accumulation represent critical challenges that extend beyond technical or policy failures, reflecting deeper ethical and moral crises in human–nature relations. This study examines how Qur’anic caliphate (khalīfah) values can be operationalized through zero waste practices, bridging normative Islamic ethics and contemporary environmental action. Using a qualitative normative–textual approach within an ecological tafsīr framework, Qur’anic verses on stewardship, balance (mīzān), moral trust (amānah), and prohibitions against excess (isrāf) and environmental destruction (fasād) were thematically analyzed alongside classical and contemporary exegeses. The findings reveal that zero waste embodies a practical manifestation of Qur’anic ethics, translating khalīfah, mīzān, and amānah into actionable environmental behaviors, including consumption reduction, waste prevention, reuse, recycling, and organic waste management. This operational mapping demonstrates that ecological responsibility is an inherent dimension of Islamic ethical teachings, offering a systematic framework for implementing value-based sustainability practices. The study contributes theoretically by advancing ecological tafsīr from conceptual ethics toward practice-oriented application and highlights the potential of religious principles to transform environmental behavior in contemporary Muslim contexts. Future research should investigate the empirical effectiveness of zero waste practices grounded in Qur’anic ethics and explore comparative eco-theological applications across communities.